Solidaritas Sosial dalam Cerita Anak Berbahasa Jawa pada Majalah Jaya baya - Devita Kristiani; Haris Supratno; Suyatno Suyatno (LP. Ma'arif Janggan Magetan, 2023)
This research aims to describe social solidarity in Javanese children's stories in Jaya Baya magazine. The purpose of this research was to describe 1) forms of social solidarity in Javanese children's stories in Jaya Baya magazine; 2) driving factors for social solidarity in Javanese children's stories in Jaya Baya magazine and 3) the value of social solidarity in Javanese children's stories in Jaya Baya magazine.This research uses a collection of 53 Javanese children's stories from several different authors. The entire research data is sourced from the 2017 Jaya Baya magazine in the rubric